A preparation method of self-lubricating silica gel and its application in shower head
By optimizing the formulation and preparation process of silicone materials, combined with vinyl silicone oil of different viscosity, gas-phase white carbon black and modification functional additives, the shortcomings of shower silicone materials in hydrophobicity, lubricity and anti-scaling properties are solved, and high-performance self-lubricating silicone is achieved, which significantly improves the service life and user experience of the shower.
Patent Information
- Application Number
- CN202510242665.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing shower silicone materials have shortcomings in hydrophobicity, lubricity and anti-scaling properties, resulting in clogging of the water outlet network, large friction resistance and short service life.
By optimizing the formulation and preparation process of silicone materials, vinyl silicone oil, gas-phase white carbon black and modification functional additives of different viscosity (such as nano zinc oxide undergoes multi-step surface modification treatment), a basic glue with excellent mechanical properties and processing properties is constructed, and the performance stability of the material is ensured through high-temperature treatment and curing molding processes.
It realizes the excellent hydrophobicity, self-lubricating properties and anti-scattering ability of silicone materials, significantly reduces scale adsorption and friction resistance, extends the service life of the shower, and meets environmental protection requirements.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone rubber materials, and in particular to a preparation method of self-lubricating silicone rubber and application of the self-lubricating silicone rubber in a shower head. Background Art
[0002] In modern life, shower heads are an important part of bathroom equipment, and their performance and service life directly affect the user experience. However, there are some problems with existing shower head silicone materials during use, which are mainly manifested in the following aspects:
[0003] Scaling problem: Existing silicone materials have a certain degree of hydrophilicity and are prone to adsorb impurities and dirt in the water, causing the showerhead water outlet to be blocked and affecting the water outlet effect. In addition, the ionization of silicone materials will also adsorb scaling substances in the water, further aggravating the scaling phenomenon and reducing the service life of the showerhead.
[0004] Large friction resistance: The surface friction coefficient of traditional silicone materials is relatively high, which causes the water flow to encounter greater resistance when passing through the shower head, affecting the smoothness of the water flow and the water discharge effect of the shower head. At the same time, the high friction coefficient will also increase the wear of the silicone material and reduce its durability.
[0005] Material performance limitations: Although some existing technologies attempt to improve the performance of silicone tubes by adding anti-aging agents, there is still much room for improvement in hydrophobicity and lubricity.
[0006] In summary, the existing showerhead silicone materials have deficiencies in hydrophobicity, lubricity and anti-scaling performance, and it is difficult to meet the demand for high-performance materials in modern showerheads. Therefore, developing a silicone material with excellent hydrophobicity, self-lubrication and anti-scaling ability is of great significance to improve the use effect and service life of showerheads.
[0007] The Chinese patent application with publication number CN116333495A discloses an anti-aging silicone tube for ventilation and water circulation and its preparation method, which belongs to the technical field of silicone tubes. According to weight parts, it includes the following raw materials: 100 parts of silicone rubber, 30-40 parts of white carbon black, 2-3 parts of vulcanizing agent, 6-9 parts of phenyl silicone oil, 11-15 parts of composite antioxidant, and 4-7 parts of methyl silicone resin. The invention adds a composite antioxidant to the raw materials of the silicone tube, which can combine the inorganic and organic anti-aging mechanisms, combine the advantages of the two, and have stable and efficient anti-aging performance; through grafting and compounding, an organic coating layer can be formed on the surface of the inorganic anti-aging filler to promote the uniform dispersion of the composite antioxidant in the silicone rubber; the composite antioxidant has a certain flame retardant effect, which can improve the flame retardant performance of the silicone tube to a certain extent, so that the obtained silicone tube can be used for water circulation and ventilation, improve the service life, and broaden the application scenarios of the silicone tube. However, the silicone tube prepared by this method still has room for improvement in terms of hydrophobicity, lubricity and surface resistance. It cannot effectively reduce or prevent adsorption when used in shower heads and is prone to scaling. Summary of the invention
[0008] In order to solve the deficiencies in the prior art, the present invention aims to provide a method for preparing self-lubricating silica gel and application thereof in a shower head.
[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0010] A method for preparing self-lubricating silica gel is as follows, in parts by weight:
[0011] Step 1, premixing: 70-100 parts of vinyl silicone oils of different viscosities, 10-20 parts of fumed silica, and 1-3 parts of an additive for treating fumed silica are uniformly blended in a vacuum kneader. During the blending process, nitrogen is passed through, the temperature is controlled at 50-80° C., and no vacuum is drawn or the temperature is raised to obtain a blend;
[0012] Step 2, high temperature treatment: the blend obtained in step 1 is treated in a vacuum kneader at 120-150°C for 2-6 hours to remove water vapor and low molecular weight molecules in vacuum to obtain a base rubber;
[0013] Step 3, mixing: 30-50 parts of the base rubber prepared in step 2, 0.3-0.8 parts of platinum catalyst, and 1-3 parts of modified functional additives are mixed evenly in a planetary mixer, filtered and packaged to obtain component A; 30-50 parts of the base rubber prepared in step 2, 5-15 parts of cross-linking agent, 0.4-0.6 parts of inhibitor, and 1-3 parts of modified functional additives are mixed evenly in a planetary mixer, filtered and packaged to obtain component B;
[0014] Step 4, product process: after mixing the component A and the component B prepared in step 3 in equal weight proportion, put them into a mold for curing and forming to obtain a self-lubricating silicone.
[0015] The vinyl silicone oils of different viscosities are prepared by mixing high-viscosity vinyl silicone oil, medium-viscosity vinyl silicone oil and low-viscosity vinyl silicone oil in a mass ratio of 1:1-3:6-8.
[0016] The viscosity of the high-viscosity vinyl silicone oil is 10,000 to 500,000 mPa·s, the viscosity of the medium-viscosity vinyl silicone oil is 1,000 to 10,000 mPa·s, and the viscosity of the low-viscosity vinyl silicone oil is 100 to 1,000 mPa·s.
[0017] The vacuum degree in step 2 is -0.06~-0.1MPa.
[0018] The auxiliary agent for treating fumed silica is at least one of hexamethyldisilazane, hexamethyldisiloxane and 1,3-divinyltetramethyldisilazane.
[0019] The crosslinking agent is at least one of methyl tributylacetoximate silane, vinyl tributylacetoximate silane and triallyl isocyanurate.
[0020] The inhibitor is at least one of diallyl maleate, diethyl fumarate and acetylene cyclohexanol.
[0021] The curing temperature in step 4 is 100-180°C.
[0022] The preparation method of the modified functional additive is as follows, in parts by weight:
[0023] S1. Disperse 15-25 parts of nano zinc oxide uniformly in 180-220 parts of anhydrous ethanol, then add 4-6 parts of 3-[tris(2-aminoethoxy)silyl]-1-propylamine, and stir at 80-95° C. for 1-5 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product;
[0024] S2, mixing 15 to 25 parts of the pre-treated product prepared in step S1 with 15 to 25 parts of 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid, adding 120 to 180 parts of cyclohexane as a solvent, and then adding 0.4 to 0.6 parts of tetramethylammonium hydroxide and 0.1 to 0.3 parts of 2,6-di-tert-butyl-p-cresol, heating the treatment system to 80 to 120° C., stirring for 1 to 4 hours, and after the treatment is completed, cooling, filtering, washing and drying to obtain a post-treated product;
[0025] S3, 15-25 parts of the post-treated product prepared in step S2 are mixed with 15-25 parts of oleic acid, 180-220 parts of cyclohexane are added as a solvent, the temperature is raised to 70-100° C., and the stirring treatment is performed for 3 hours. During the treatment process, the generated water and excess solvent are distilled out by a rectification device. After the treatment is completed, the remaining treated liquid is cooled, poured into 180-220 parts of water, and the pH is adjusted to neutral with a 0.1-0.3 mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive is obtained by suction filtration and drying.
[0026] The application of the self-lubricating silicone in a shower head specifically refers to the application of the silicone in the water outlet of a shower head.
[0027] In the present invention, the functions of each substance are as follows:
[0028] Vinyl silicone oils of different viscosities serve as the base component of silicone, providing flexibility and elasticity. High viscosity vinyl silicone oils increase the strength and tear resistance of silicone. Medium viscosity vinyl silicone oils balance flexibility and processing performance. Low viscosity vinyl silicone oils improve flow and dispersibility for easy processing and mixing.
[0029] Fumed silica acts as a reinforcing agent to improve the mechanical properties of silicone, such as tensile strength, abrasion resistance and tear resistance.
[0030] Additives for treating fumed silica improve the dispersion of fumed silica, prevent its agglomeration, and enhance its compatibility with silicone oil.
[0031] Platinum catalyst acts as a catalyst to accelerate the vulcanization reaction of silicone and ensure that the material takes shape quickly during the curing process.
[0032] Cross-linking agents promote cross-linking between silicone molecular chains to form a three-dimensional network structure, thereby enhancing the mechanical properties and heat resistance of the material.
[0033] Inhibitors control the speed of the vulcanization reaction, preventing premature curing and ensuring smooth processing.
[0034] Nano zinc oxide is mainly used as an antibacterial agent, ultraviolet absorber and inorganic filler in the present invention. At the same time, the hydrophobicity, lubricity and mechanical properties of silica gel are enhanced through surface modification, thereby improving the comprehensive performance of the material and meeting environmental protection requirements.
[0035] 3-[Tris(2-aminoethoxy)silyl]-1-propylamine chemically bonds with the hydroxyl groups on the surface of nano-zinc oxide through the amino group, thereby enhancing the dispersibility and surface activity of nano-zinc oxide.
[0036] 11-[4,6,8-tri(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid reacts with the amino group through the long chain carboxyl group to form a stable chemical bond, further enhancing the organic modification layer on the surface of nano-zinc oxide.
[0037] Oleic acid further reacts with the modified nano zinc oxide to form a hydrophobic surface layer, which enhances the lubricity and hydrophobicity of the material.
[0038] Cyclohexane is used as a solvent to dissolve and disperse the components in the modified functional additives to ensure the smooth progress of the reaction.
[0039] Tetramethylammonium hydroxide is used as a catalyst to promote the reaction and accelerate the synthesis of the modified functional additive.
[0040] 2,6-Di-tert-butyl-p-cresol is used as an inhibitor to prevent the occurrence of side reactions during the reaction and ensure the stability and controllability of the reaction.
[0041] The pH value is adjusted by sodium hydroxide aqueous solution to ensure that the final product of the modified functional additive is neutral and avoid adverse effects on the silica gel matrix.
[0042] Anhydrous ethanol is used as a dispersion medium for the pretreatment of nano zinc oxide to ensure its uniform dispersion.
[0043] These substances work synergistically, through optimized formula and process, to achieve the excellent hydrophobicity, self-lubricating properties and anti-scaling ability of silicone materials, while meeting environmental protection requirements. It is particularly suitable for application scenarios such as shower heads that require high-performance materials.
[0044] Compared with the prior art, it has the following beneficial effects:
[0045] 1) The present invention significantly improves the hydrophobicity of the silica gel material through the design of a special modified functional additive. The modified silica gel surface can effectively reduce the adsorption of water molecules and the adhesion of impurities and dirt in the water, thereby effectively solving the problem of showerhead water outlet network blockage and extending the service life of the showerhead.
[0046] 2) The self-lubricating silica gel of the present invention achieves an extremely low friction coefficient by optimizing the surface properties. After multiple water washings, its friction coefficient can still be maintained at a low level, which is significantly better than the existing technology. This low friction coefficient not only improves the smoothness of water flow, but also reduces material wear and enhances the durability of the product.
[0047] 3) The silica gel material of the present invention has a high surface resistance, which can effectively reduce surface ionization and further reduce scale adsorption. In addition, the material does not contain harmful substances such as fluorine, heavy metals and halogens, meets environmental protection requirements, is friendly to the human body and the environment, and is particularly suitable for application scenarios with high requirements for environmental protection and safety. DETAILED DESCRIPTION
[0048] Main sources of substances:
[0049] High viscosity vinyl silicone oil, viscosity (25℃): 10000mPa·s; medium viscosity vinyl silicone oil, viscosity (25℃): 1000mPa·s; low viscosity vinyl silicone oil, viscosity (25℃): 350mPa·s.
[0050] Platinum catalyst, CAS: 68478-92-2, Shanghai Bozhijie New Materials Co., Ltd.
[0051] Fumed silica, model: TS720, brand: Cabot.
[0052] Nano zinc oxide, product number 544906, particle size <100 nm, was sourced from Merck.
[0053] Hydroxy silicone oil, model: PMX-0156, viscosity (cSt): 50-120, brand: Dow.
[0054] Carboxypropyl terminated polydimethylsiloxane, CAS number: 158465-59-9.
[0055] 3-[tris(2-aminoethoxy)silyl]-1-propanamine, CAS No.: 1134640-02-0, English name: 3-[tris(2-aminoethoxy)silyl]-1-propanamine, molecular formula: C9H 26 N4O3Si.
[0056] 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilocan-2-yl]undecanoic acid, CAS: 158038-52-9, English name: 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilocan-2-yl]undecanoic acid, molecular formula: C 48 H 96 O 12 Si4.
[0057] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.
[0058] The design idea of the present invention is to develop a self-lubricating silica gel with excellent hydrophobicity, self-lubricating performance and anti-scaling ability by optimizing the formula and preparation process of silica gel materials. Specifically, by selecting vinyl silicone oils of different viscosities for compounding, combining fumed silica and specific processing additives, a base glue with excellent mechanical properties and processing properties is constructed. At the same time, specially modified functional additives (such as nano zinc oxide after multi-step surface modification) are introduced to further enhance the hydrophobicity and lubricity of silica gel. In addition, the performance stability and consistency of the material are ensured by precisely controlling the high-temperature treatment and curing molding process. Ultimately, this self-lubricating silica gel material can effectively reduce scale adsorption, reduce the surface friction coefficient, and improve the service life and user experience of bathroom products such as shower heads. At the same time, it meets environmental protection requirements and has broad application prospects.
[0059] Example 1
[0060] A method for preparing self-lubricating silica gel is as follows:
[0061] Step 1, premixing: 80 parts by weight of vinyl silicone oils of different viscosities, 15 parts by weight of fumed silica, and 2 parts by weight of hexamethyldisilazane are uniformly blended in a vacuum kneader. During the blending process, nitrogen is passed through, the temperature is controlled at 80° C., and no vacuum is drawn or the temperature is raised to obtain a blend;
[0062] Step 2, high temperature treatment: the blend obtained in step 1 is treated in a vacuum kneader at 140°C for 4 hours, and water vapor and low molecules are removed by vacuum, and the vacuum degree is -0.08MPa, to obtain a base rubber;
[0063] Step 3, mixing: 40 parts by weight of the base rubber prepared in step 2, 0.5 parts by weight of a platinum catalyst, and 2 parts by weight of a modified functional additive are mixed evenly in a planetary mixer, filtered and packaged to obtain component A; 40 parts by weight of the base rubber prepared in step 2, 10 parts by weight of methyl tributylidene oxime silane, 0.5 parts by weight of diallyl maleate, and 2 parts by weight of a modified functional additive are mixed evenly in a planetary mixer, filtered and packaged to obtain component B;
[0064] Step 4, product process: after mixing the component A and the component B prepared in step 3 in equal weight proportions, put them into a mold and solidify them at 115° C. to obtain a self-lubricating silicone.
[0065] The vinyl silicone oils of different viscosities are prepared by mixing high-viscosity vinyl silicone oil, medium-viscosity vinyl silicone oil and low-viscosity vinyl silicone oil in a mass ratio of 1:2:7.
[0066] The preparation method of the modified functional additive is as follows:
[0067] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of 3-[tris(2-aminoethoxy)silyl]-1-propylamine, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0068] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0069] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0070] Example 2
[0071] The preparation method of a self-lubricating silica gel is basically the same as that of Example 1, the only difference being that the preparation method of the modified functional additive is different.
[0072] The preparation method of the modified functional additive is as follows:
[0073] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of 3-aminopropyltris(methoxyethoxyethoxy)silane, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0074] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0075] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0076] Example 3
[0077] The preparation method of a self-lubricating silica gel is basically the same as that of Example 1, the only difference being that the preparation method of the modified functional additive is different.
[0078] The preparation method of the modified functional additive is as follows:
[0079] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of 3-[tri(2-methoxyethoxy)silyl]propan-1-amine, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0080] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0081] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0082] Example 4
[0083] The preparation method of a self-lubricating silica gel is basically the same as that of Example 1, the only difference being that the preparation method of the modified functional additive is different.
[0084] The preparation method of the modified functional additive is as follows:
[0085] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of 3-[tris(2-aminoethoxy)silyl]-1-propylamine, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0086] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of hydroxy silicone oil, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0087] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0088] Example 5
[0089] The preparation method of a self-lubricating silica gel is basically the same as that of Example 1, the only difference being that the preparation method of the modified functional additive is different.
[0090] The preparation method of the modified functional additive is as follows:
[0091] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of 3-[tris(2-aminoethoxy)silyl]-1-propylamine, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0092] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0093] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0094] Comparative Example 1
[0095] The preparation method of a self-lubricating silica gel is basically the same as that of Example 1, the only difference being that the preparation method of the modified functional additive is different.
[0096] The preparation method of the modified functional additive is as follows:
[0097] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of γ-aminopropyltriethoxysilane, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0098] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0099] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0100] Comparative Example 2
[0101] The preparation method of a self-lubricating silica gel is basically the same as that of Example 1, the only difference being that the preparation method of the modified functional additive is different.
[0102] The preparation method of the modified functional additive is as follows:
[0103] S1. Disperse 20 g of nano zinc oxide uniformly in 200 g of anhydrous ethanol, then add 5 g of 3-[tris(2-aminoethoxy)silyl]-1-propylamine, and stir at 90° C. for 3 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product.
[0104] S2, 20g of the pre-treated product prepared in step S1 was mixed with 20g of carboxypropyl-terminated polydimethylsiloxane, 150g of cyclohexane was added as a solvent, and 0.5g of tetramethylammonium hydroxide and 0.2g of 2,6-di-tert-butyl-p-cresol were added, the treatment system was heated to 100°C, stirred for 3 hours, and after the treatment was completed, cooled, filtered, washed and dried to obtain a post-treated product;
[0105] S3, 20g of the post-treated product prepared in step S2 was mixed with 20g of oleic acid, 200g of cyclohexane was added as a solvent, the temperature was raised to 90°C, and the mixture was stirred for 3 hours. During the treatment, the generated water and excess solvent were distilled out by a rectification device. After the treatment, the remaining treated liquid was cooled and poured into 200g of water. The pH was adjusted to neutral with a 0.2mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive was obtained by suction filtration and drying.
[0106] Comparative Example 3
[0107] A method for preparing a self-lubricating silica gel is substantially the same as that of Example 1, the only difference being that the modified functional agent is replaced with an equal amount of nano zinc oxide.
[0108] Test Example 1
[0109] Hydrophobicity test
[0110] The self-lubricating silica gel prepared by the present invention was tested for water contact angle using a contact angle analyzer, with a water volume of 5 μL, and the data were taken after the water droplet was in contact with the self-lubricating silica gel for 60 seconds. The larger the contact angle between the material and the water surface, the better its hydrophobicity. The specific test data are shown in Table 1.
[0111] Table 1 Hydrophobicity test results
[0112] Test Example 2
[0113] Lubricity test
[0114] The present invention uses an MXD-02 friction coefficient tester to test the friction coefficient of the self-lubricating silica gel prepared by the present invention: the self-lubricating silica gel after 30 times of water washing is immersed in water for 30 seconds, and then fixed on the groove plate, and water is injected into the water tank until the sample is completely immersed therein. A 200g standard slider is gently placed above the sample, and the slider is dragged by the sensor connecting rod to move at a speed of 100mm / min to measure the dynamic friction coefficient. The test results are shown in Table 2.
[0115] Table 2 Lubricity test results
[0116] Test Example 3
[0117] Surface resistance test
[0118] The surface resistance of the self-lubricating silica gel prepared by the present invention was tested with reference to GB / T 31838.4-2019 "Dielectric and resistance properties of solid insulating materials Part 4: Resistance properties (DC method) Insulation resistance". The test results are shown in Table 3.
[0119] Table 3 Surface resistance test results
[0120] It can be seen from the data of test examples 1 to 3 that the self-lubricating silica gel prepared in Example 1 has the best hydrophobicity, lubricity and surface resistance.
[0121] In the present invention, the 3-[tris(2-aminoethoxy)silyl]-1-propylamine used in Example 1 shows significant advantages in the preparation of modified functional additives, especially in terms of hydrophobicity, lubricity and surface resistance. First, the 3-[tris(2-aminoethoxy)silyl]-1-propylamine molecule contains multiple aminoethoxy (-NH2 and -OCH2CH2-) units, which give the molecule higher polarity and processing activity. In the pretreatment process with nano zinc oxide, the amino group can chemically bond with the hydroxyl group (-OH) on the surface of nano zinc oxide to form a stable structure, thereby enhancing the dispersibility and compatibility of nano zinc oxide in the organic matrix. This chemical bonding not only improves the surface activity of nano zinc oxide, but also provides more active sites for subsequent treatment. Secondly, the aminoethoxy unit in the 3-[tris(2-aminoethoxy)silyl]-1-propylamine molecule has a long flexible chain structure, which enables the surface of the nano zinc oxide to form an organic layer with a certain steric hindrance after modification. This organic layer can effectively reduce the direct contact between nano zinc oxide and water molecules, thereby improving the hydrophobicity of the material. In subsequent treatments, this flexible chain structure can also be cross-linked with carboxyl-terminated siloxane or oleic acid to form a denser network structure, further enhancing the hydrophobicity and lubricity of the material, and can also effectively adjust the surface resistance of the material. Since the flexible chain structure of the aminoethoxy unit can limit the free movement of charges, the surface resistance of the material is increased to a certain extent. This higher surface resistance helps to reduce the ionization of the material surface, further reduce the adsorption and scaling of water molecules, and thus improve the self-lubricating properties of the material. In contrast, although 3-aminopropyltri(methoxyethoxyethoxy)silane in Example 2, 3-[tri(2-methoxyethoxy)silyl]propan-1-amine in Example 3, and γ-aminopropyltriethoxysilane in Comparative Example 1 also have certain treatment activity, they are not as good as 3-[tri(2-aminoethoxy)silyl]-1-propylamine in enhancing the dispersibility, hydrophobicity and surface resistance of nano-zinc oxide due to the lack of sufficient flexible chains or the small number of aminoethoxy units in their molecular structures.
[0122] The 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxa tetrasilane-2-yl]undecanoic acid used in Example 1 shows significant superiority in the preparation of modified functional additives, especially in terms of hydrophobicity, lubricity and surface resistance. The 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxa tetrasilane-2-yl]undecanoic acid molecule contains multiple long-chain carboxyl groups (-COOH) and tetraoxa tetrasilane groups, which gives it excellent treatment activity and surface modification ability. During the modification process, the long-chain carboxyl group can be esterified with the amino group to form a stable amide bond, thereby constructing an organic modification layer on the surface of nano zinc oxide. This modified layer not only enhances the compatibility of nano zinc oxide with the silica gel matrix, but also significantly improves the hydrophobicity of the material through its hydrophobic long-chain structure. In addition, the tetraoxa tetrasilane group further enhances its cross-linking ability with the silica gel matrix. This cross-linking effect not only improves the mechanical properties of the material, but also increases the surface resistance of the material by limiting the movement of charge carriers. Higher surface resistance helps to reduce the ionization of the material surface, thereby reducing the adsorption and scaling of water molecules, and further improving the self-lubricating properties of the material. In contrast, although the hydroxy silicone oil in Example 4 and the 1,3-bis(3-carboxypropyl)tetramethyldisiloxane in Example 5 also have certain treatment activity, due to the lack of sufficient long-chain carboxyl groups and complex siloxane groups in their molecular structures, their performance in hydrophobicity, lubricity and surface resistance is not as good as that in Example 1. The carboxypropyl-terminated polydimethylsiloxane in Comparative Example 2 cannot provide sufficient hydrophobicity and surface resistance due to its lower cross-linking ability.
Claims
1. A method for preparing self-lubricating silica gel, characterized in that: The method is as follows, in parts by weight: Step 1, premixing: 70-100 parts of vinyl silicone oils of different viscosities, 10-20 parts of fumed silica, and 1-3 parts of an additive for treating fumed silica are uniformly blended in a vacuum kneader. During the blending process, nitrogen is passed through, the temperature is controlled at 50-80° C., and no vacuum is drawn or the temperature is raised to obtain a blend; Step 2, high temperature treatment: the blend obtained in step 1 is treated in a vacuum kneader at 120-150°C for 2-6 hours to remove water vapor and low molecular weight molecules in vacuum to obtain a base rubber; Step 3, mixing: 30-50 parts of the base rubber prepared in step 2, 0.3-0.8 parts of platinum catalyst, and 1-3 parts of modified functional additives are mixed evenly in a planetary mixer, filtered and packaged to obtain component A; 30-50 parts of the base rubber prepared in step 2, 5-15 parts of cross-linking agent, 0.4-0.6 parts of inhibitor, and 1-3 parts of modified functional additives are mixed evenly in a planetary mixer, filtered and packaged to obtain component B; Step 4, product process: after mixing the component A and the component B prepared in step 3 in equal weight proportion, put them into a mold for curing and forming to obtain a self-lubricating silicone.
2. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The vinyl silicone oil is a mixture of high-viscosity vinyl silicone oil, medium-viscosity vinyl silicone oil, and low-viscosity vinyl silicone oil in a mass ratio of 1:1-3:6-8; The viscosity of the high-viscosity vinyl silicone oil is 10,000 to 500,000 mPa·s, the viscosity of the medium-viscosity vinyl silicone oil is 1,000 to 10,000 mPa·s, and the viscosity of the low-viscosity vinyl silicone oil is 100 to 1,000 mPa·s.
3. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The vacuum degree of the vacuum kneader in step 2 is -0.06 to -0.1 MPa.
4. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The auxiliary agent for treating fumed silica is at least one of hexamethyldisilazane, hexamethyldisiloxane and 1,3-divinyltetramethyldisilazane.
5. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The crosslinking agent is at least one of methyl tributylacetoximate silane, vinyl tributylacetoximate silane and triallyl isocyanurate.
6. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The inhibitor is at least one of diallyl maleate, diethyl fumarate and acetylene cyclohexanol.
7. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The curing temperature in step 4 is 100-180°C.
8. The method for preparing the self-lubricating silica gel according to claim 1, characterized in that: The preparation method of the modified functional additive is as follows, in parts by weight: S1. Disperse 15-25 parts of nano zinc oxide uniformly in 180-220 parts of anhydrous ethanol, then add 4-6 parts of 3-[tris(2-aminoethoxy)silyl]-1-propylamine, and stir at 80-95° C. for 1-5 hours. After the treatment, filter, wash with alcohol, and dry the product to obtain a pretreated product; S2, mixing 15 to 25 parts of the pre-treated product prepared in step S1 with 15 to 25 parts of 11-[4,6,8-tris(10-carboxydecyl)-2,4,6,8-tetramethyl-1,3,5,7,2,4,6,8-tetraoxatetrasilane-2-yl]undecanoic acid, adding 120 to 180 parts of cyclohexane as a solvent, and then adding 0.4 to 0.6 parts of tetramethylammonium hydroxide and 0.1 to 0.3 parts of 2,6-di-tert-butyl-p-cresol, heating the treatment system to 80 to 120° C., stirring for 1 to 4 hours, and after the treatment is completed, cooling, filtering, washing and drying to obtain a post-treated product; S3, 15-25 parts of the post-treated product prepared in step S2 are mixed with 15-25 parts of oleic acid, 180-220 parts of cyclohexane are added as a solvent, the temperature is raised to 70-100° C., and the stirring treatment is performed for 3 hours. During the treatment process, the generated water and excess solvent are distilled out by a rectification device. After the treatment is completed, the remaining treated liquid is cooled, poured into 180-220 parts of water, and the pH is adjusted to neutral with a 0.1-0.3 mol / L sodium hydroxide aqueous solution. Finally, the modified functional additive is obtained by suction filtration and drying.
9. A self-lubricating silica gel, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. The use of the self-lubricating silica gel in a shower head as claimed in claim 9, characterized in that: Application of silicone in the water outlet of shower heads.
Citation Information
Patent Citations
Anti-aging silicone tube for ventilation and water supply and preparation method of anti-aging silicone tube
CN116333495A
Cited By
Silicone rubber material for shower head and preparation method thereof
CN121160095A